QUANTIFICATION OF FLUVIAL INCISION OF DOURO RIVER TRIBUTARIES (NE PORTUGAL) - BASE LEVEL, DIFFERENTIAL UPLIFT AND LITHOLOGICAL CONTROLS ON THE RIVERS LONG PROFILE EVOLUTION - Martins, António (2015)
This study analyses the long profiles of the Águeda, Côa, Távora and Paiva rivers, and of other Douro River lower order tributaries. The Águeda and Côa rivers flow encased on the vast planation surface that characterizes the Hesperian Massif morphology (the Iberian Meseta), while the Távora and Paiva rivers flow through higher, uplifted blocks, located west of the Vilariça fault zone (VFZ). These streams flow through a landscape strongly influenced by variations in bedrock lithology (granites and metasediments), fault structures that promoted differential uplift, and significant base-level changes. The longitudinal profiles of the Douro tributaries commonly display concavities separated by knickpoints/knickzones. The most upstream concavity reflects a relict graded profile of probable Piacenzian – Gelasian age, testifying an Atlantic exoreic drainage coeval of a high sea-level. Downstream concavities reflect the on-going transmission of several incision waves, linked to the Pleistocene - present stage of fluvial incision. In downstream concavities, the stream is graded to transient forms of the river profile with respect to the lithology, structure and base level history. They alternate with convexities (knickzones) developed where the incision waves were delayed, pinned to granite contacts. The amount of incision that postdates the relict graded profile, obtained by downstream extrapolation of the relict concave reach to the confluence with the trunk river, varies from ca. 400-450 m in the Iberian Meseta (east of the VFZ) to more than 600-650 m in the more uplifted blocks at the west. However, east of the VFZ, the amount of incision inferred by this procedure overestimates the incision measured from the surface of Meseta which is here located below the extrapolated relict long profiles by an amount that reaches ca. 120 m at the River Côa mouth. This overestimation supports: a) a northwards tilting of the Iberia Meseta in this area since the Late Miocene; b) the differential uplift along the VFZ, resulting from a northwards increase of the relative downthrowing of the eastern block of this fault; c) the exhumation of the Iberian Meseta by removal of a Cenozoic cover, whose thickness would be equivalent to the difference in height between the projected relict profile and the Meseta surface. The larger incision (525 and 477 m) inferred at the Águeda and Aguiar stream mouths is associated with long term enhanced uplift of the Iberian Meseta. For the last ca. 2 Ma (beginning of the incision stage?) incision rates can range from 0.2 mm/yr in the less uplifted compartments to 0.6 mm/yr in the more uplifted blocks (west of the VFZ). This work is in the scope of proj. PTDC/GEO-GEO/2860/2012